Elevage de Solea senegalensis (Kaup, 1958) en Tunisie - Bedoui R. (Marine aquaculture finfish species diversification, 1995)
Solea senegalensis was reared at the laboratory scale. The rearing was conducted from the broodstock to the juvenile of 2 months. The broostock was collected from the wild, acclimatised in a race ways with a sand bottom. The natural spawning was obtained at 18 degrees C during 3 months, April, May and June. The pelagic egg size was ranged between 0.996 and 1.025 mm. The incubation realized in stagnant water lasted 42 hours at 19 degrees C. The larval rearing was conducted to 2 months, larvae were fed exclusively on live artemia then on frozen artemia at the weaning. Ontogeny of sole larvae was monitored from the egg stage to the juvenile stage. The digestive system was followed during the larval development. Methamorphosis larvae tolerate fresh water and survive normally. The ingested preys increase with the increasing of the larval age and the prey densities. Starvation does not affect the ingested capacity.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1995/06/14-17, Nicosia (Cyprus)